A study on factors contribute to level of job satisfaction among employees at Paediatric Department, Hospital Melaka / Steve Morgan Anak Lisin and Nor Amy Hassan - Lisin, Steve Morgan; Hassan, Nor Amy (Faculty of Administrative Science and Policy Studies, 2013)
Understanding the factors contribute to level of job satisfaction among employees is significance because satisfied employees will improve overall effectiveness and successfulness of an organization. The Paediatric Department, Hospital Melaka plays a crucial role as one of the government agency under the Ministry of Health in achieving the targets outlined in the policy. However, a lack of attention has been focused on understanding the factors that influence the level of job satisfaction among the department’s employees. The research focused on the level of job satisfaction by looking from three different performance appraisal, promotion and reward/salary. Thus, the main objective of this research is to study the factors contribute to level of job satisfaction among employees at Paediatric Department, Hospital Melaka and to verify whether the factor influenced the level of job satisfaction. A survey was developed and utilized to gather data regarding the importance of the factors to employees’ level of job satisfaction. The total of 32 respondents has participated in the research from overall 35 employees of the department using simple random sampling technique. The instruments has been developed and adapted from several of previously known researches. The data that was gathered was statistically analyzed in order to support or reject the research hypotheses by using the SPSS software. The findings of the research indicated that the respondents generally are satisfied with their job. In addition, gender factor do not influence the level of job satisfaction. Limitations and recommendations on the study are also discussed.